2019
DOI: 10.1002/nau.24160
|View full text |Cite
|
Sign up to set email alerts
|

The effects of microenergy acoustic pulses on an animal model of obesity‐associated stress urinary incontinence. Part 1: Functional and histologic studies

Abstract: Aim Obesity is a strong independent risk factor for urinary incontinence. Effective therapeutic approaches for obesity‐associated stress urinary incontinence (OA‐SUI) are lacking as the mechanisms remain unclear. The aim of our study is to explore the impacts of microenergy acoustic pulse (MAP) therapy on urethral and pelvic floor muscle structure and function in female lean and fatty rats. Methods A total 24 Zucker fatty (ZF) and 24 Zucker lean (ZL) female 24‐week‐old rats were grouped into four groups: ZL co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…24,32 In addition, our previous work shows that muscle stem/progenitor cells can be activated (using microenergy acoustic pulses [MAP]) for urethral stM regeneration, thus improving urinary function. 35,36 StMs were found throughout the main portion of the…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,32 In addition, our previous work shows that muscle stem/progenitor cells can be activated (using microenergy acoustic pulses [MAP]) for urethral stM regeneration, thus improving urinary function. 35,36 StMs were found throughout the main portion of the…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, we reported that MAP treatment restored micturition function in ZF rats via activation of muscle stem/progenitor cells to regenerate the urethral sphincter muscle. 35,36 With the goal of finding alternative, potentially more effective, efficient ways to accomplish this task, we applied CRISPRi/MSTN system in the OA-SUI animal model in vivo. Strikingly, 4 weeks after the delivery of CRISPRi/MSTN system in the urethral tissue, the LPP significantly improved by twofold in the ZF rats.…”
mentioning
confidence: 99%
“…The application of MAP treatment was performed on the same hindlimb at 1 week after the initial injury by using a compact electromagnetic unit with an unfocused acoustic pulse source (LiteMed Inc.). 9 Animals were under general anesthesia and the shock wave probe was applied directly to the shaved tibialis anterior (TA) muscles and was coupled to the skin using ultrasound gel (Aquasonic, Parker Laboratories Inc.). The MAP had an energy flux density at 0.059 mJ/mm 2 , and 500 pulses were delivered at 3 Hz.…”
Section: Animals and Proceduresmentioning
confidence: 99%
“…7 Recently, an improved technology of Li-ESWT named microenergy acoustic pulses (MAP) has been developed. 8,9 Compared to the traditional Li-ESWT and other shock wave-based therapies, the beam of the acoustic pulses of MAP is defocused to allow more even energy distribution to the treated tissue and eliminates the potential damage to issue at focal point. 10 We discovered that MAP ameliorated stress urinary incontinence (SUI) by enhancing regeneration of striated muscles in the external urinary sphincter and pelvic floor in rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation